The evolving maritime balance of power in the Asia-Pacific : maritime doctrines and nuclear weapons at sea - Prabhakar, Lawrence W.; Ho, Joshua; Bateman, W. S. G. (Walter Samuel Grono) (World Scientific ; Institute of Defence and Strategic Studies, 2006)
The Asia-Pacific region has emerged as the hub of global geo-political, geo-economic and geo-strategic significance in the post-Cold War period. The rise of China and the resurgence of India will be the hallmark for the next 50 years. How this surge in power is accommodated by the incumbent powers like the United States and Japan, and how the new regional powers like China and India manage the power politics that emerge will be the key determinants of regional stability. This volume examines the national maritime doctrines as well as the nuclear weapons developments at sea of the four major powers in the Asia-Pacific, namely, China, India, Japan and the United States, to see if the evolving dynamic is a cooperative or a competitive one. In particular, the volume looks at the evolving paradigms of maritime transformation in strategy and technology; the emergent new maritime doctrines and evolving force postures in the naval orders of battle; the role and operations of nuclear navies in the Asia-Pacific; and the implications and impact of nuclear weapons, ballistic missiles and sea-based missile defence responses in the region. Sample Chapter(s)Chapter 1: Cooperation or Competition in Maritime Asia-Pacific? (544 KB)Chapter 3: Maritime Strategic Trends in the Asia-Pacific: Issues and Challenges (1,534 KB) Contents:Issues, Trends and Paradigms in Maritime Asia-PacificNational Maritime Doctrines and CapabilitiesNuclear Weapons and Missile Defences: The Maritime Dimension in the Asia-PacificReadership: Policy makers, academics, research analysts and students interested in maritime security in the Asia-Pacific region.